2020
DOI: 10.3390/s20174741
|View full text |Cite
|
Sign up to set email alerts
|

Use of Predicted Behavior from Accelerometer Data Combined with GPS Data to Explore the Relationship between Dairy Cow Behavior and Pasture Characteristics

Abstract: Our aim in this study was to investigate whether the behaviors of dairy cows on pasture, predicted with accelerometer data and combined with GPS data, can be used to better understand the relationship between behaviors and pasture characteristics. During spring 2018, 26 Holstein cows were equipped with a 3D-accelerometer and a GPS sensor fixed on a neck-collar for five days. The cows grazed alternatively in permanent and in temporary grasslands. The structural elements, soil moisture, slope and botanical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…Actually, the elevation of the watering sites and the horizontal distance to the water are significant predictors of livestock grazing distribution (these two variables negatively correlate to the frequency of visits to the water sources) [ 28 ]. Grazing animals typically prefer to ruminate and rest in small areas close to water troughs [ 10 ] or trees [ 29 ], although grazing hotspots are also recognised near to water points [ 10 , 29 ].…”
Section: Effect Of External Factors On Site Use Preferencementioning
confidence: 99%
“…Actually, the elevation of the watering sites and the horizontal distance to the water are significant predictors of livestock grazing distribution (these two variables negatively correlate to the frequency of visits to the water sources) [ 28 ]. Grazing animals typically prefer to ruminate and rest in small areas close to water troughs [ 10 ] or trees [ 29 ], although grazing hotspots are also recognised near to water points [ 10 , 29 ].…”
Section: Effect Of External Factors On Site Use Preferencementioning
confidence: 99%
“…Foldager [38] uses accelerometers and radio frequency identification (RFID) prototype devices installed on the collar to collect data, and detects the feed intake and feeding time of dairy cows, with an accuracy of more than 85%. Riaboff [39] collected the acceleration and GPS data of dairy cows and comprehensively detected the behavior of dairy cows in the pasture. They found that in permanent grassland, dairy cows ruminate and rest under trees for a longer time, and in fluffy grass ( Holcus lanatus) area has more grazing time; on the temporary grassland, the conclusion that behavior is easily affected by the external environment.…”
Section: B Comparison Of Test Resultsmentioning
confidence: 99%
“…Drinking behavior has been reported in studies with a controlled environment [ 9 ] and in general the authors suggested further studies and adaptations for better drinking behavior predictions [ 10 ]. Additionally, the majority of results reported for animal behavior prediction using accelerometer information is with a taurine genetic composition [ 11 , 12 , 13 , 14 ], which can be different from a zebu genetic composition, due to the differences in temperament [ 15 ].…”
Section: Introductionmentioning
confidence: 99%